Estimating Long-Term Mating Systems Using DNA Sequences - Milligan, B. G. (1996)
Plant mating systems often involve a mixture of self fertilizations and outcross fertilizations. The degree of selfing has a large impact on the genetic composition of natural populations and on the evolution of the mating system itself in response to such factors as inbreeding depression. This paper describes a means of estimating the long-term rate of self-fertilization from samples of alleles taken from individuals in a population. Use is made of the genealogy of pairs of alleles at a locus within individuals and pairs between individuals. The degree of selfing is closely related to the extent to which the number of nucleotide sites differing within an individual is reduced relative to the number differing between individuals. Importantly, the estimate of long-term selfing is largely independent of population size and is not affected by historical fluctuations in population size; instead it responds directly to the mating system itself. The approach outlined here is most appropriate to evolutionary problems in which the long-term nature of the mating system is of interest, such as to determine the relationship between prior inbreeding and inbreeding depression.